Involvement of calpains in adult neurogenesis: implications for stroke - Machado, Vanessa M.; Morte, Maria I.; Carreira, Bruno P.; Azevedo, Maria M.; Takano, Jiro; Iwata, Nobuhisa; Saido, Takaomi C.; Asmussen, Hannelore; Horwitz, Alan R.; Carvalho, Caetana M.; Araújo, Inês M. (Frontiers in Cellular Neuroscience, 2015)
Calpains are ubiquitous proteases involved in cell proliferation, adhesion and motility. In the brain, calpains have been associated with neuronal damage in both acute and neurodegenerative disorders, but their physiological function in the nervous system remains elusive. During brain ischemia, there is a large increase in the levels of intracellular calcium, leading to the activation of calpains. Inhibition of these proteases has been shown to reduce neuronal death in a variety of stroke models. On the other hand, after stroke, neural stem cells increase their proliferation and newly formed neuroblasts migrate towards the site of injury. However, the process of forming new neurons after injury is not efficient and finding ways to improve it may help with recovery after lesion. Understanding the role of calpains in the process of neurogenesis may therefore open a new window for the treatment of stroke. We investigated the involvement of calpains in neural stem cell proliferation and neuroblast migration in two highly neurogenic regions in the mouse brain, the dentate gyrus and the subventricular zone. We used mice that lack calpastatin, the endogenous calpain inhibitor, and calpains were also modulated directly, using calpeptin, a pharmacological calpain inhibitor. Calpastatin deletion impaired both neural stem cell proliferation and neuroblast migration. Calpain inhibition increased neural stem cell proliferation, migration speed and migration distance in cells from the subventricular zone. Overall, our work suggests that calpains are important for neurogenesis and warrant further research on how they influence the formation of new neurons. Prospective therapies targeting calpain activity not only may afford neuroprotection following stroke, but also benefit the formation and survival of new neurons.